EFFECTS OF KINESIOLOGICAL ACTIVITIES OF DIFFERENT EXTENSITY ON BOYS 'BASIC- MOTOR ABILITIES - Mensur Halilovic; Osman Lačić; Jasmin Bilalić; Nermin Salkanovic (Sport Scientific And Practical Aspects, 2025)
The goal of this research is to evaluate the effects of applied kinesiological activities of different extensions on the transformation of basal-motor abilities of boys. The sample of respondents is represented by boys, students of VII, VIII and IX grades of primary school. „21. March "Matuzići - Doboj South. The total sample consists of a set of 76 respondents classified into three distinct groups. Based on the boys' statements about their participation in everyday physical activities, groups with the numbering were defined through non-athletes: non-athletes-1, recreational athletes-2 and athletes-3. To assess the basic motor skills of the respondents, the variables according to the Eurofit battery test program were used, as follows: Flamingo balance, endurance in the joint, lying-sitting, running 10 × 5m (back and forth), hand tapping, hand dynamometry, flexibility-mobility at the hip joint, jumping away from the spot and running 20m back and forth with progressive acceleration. The results of univariate covariance analysis showed high significance in endurance assessment tests (SHATL 20 and SHATL 10 × 5), followed by static arm strength (MSSIZG), and hand strength (MSSDIN) and torso flexibility (MFLPRK) and balance (MRFLAM). Statistically significant differences in effects did not occur with the three variables, namely hand tapping ( MBFTAR), long jump (MESSDM) or squat-sitting (MRSLSJ)..